Landscapes of Music in Istanbul : A Cultural Politics of Place and Exclusion (Edition 1) - Papadopoulos, Alex G.; Duru, Asli (2017)
Everyday articulations of music, place, urban politics, and inclusion/exclusion are powerfully present in Istanbul. This volume analyzes landscapes of music, community, and exclusion across a century and a half. An interdisciplinary group of scholars and artists presents four case studies: the rembetika, the music of the Asiks, the Zakir/Alevi tradition, and hip-hop, in Beyoglu, Üsküdar, the gentrifying Sulukule neighborhood, and across the metropolis.